Fentanyl vs dexmedetomidine nebulization as adjuvant to lignocaine: A comparative study during awake flexible fiberoptic bronchoscopy. (April 2021) - Kumari, Poonam; Kumar, Amarjeet; Sinha, Chandni; Kumar, Ajeet; Rai, Deependra Kumar; Kumar, Rajesh
Abstract: Background and aims: Flexible fiberoptic bronchoscopy is used to diagnose diseases of the tracheobronchial tree and to obtain samples. Methods used for awake flexible fiberoptic bronchoscopy (FFB) to anaesthetize the airway include local anaesthetic nebulization, gargles, lozenges, sprays, and airway blocks. The aim is to compare the effect of fentanyl and dexmedetomidine nebulization as an adjuvant to lignocaine during awake FFB. Methods: Ninety patients were recruited and were randomized into 3 groups. Group I Patients were nebulised with a mixture of 4% lignocaine 4 ml and fentanyl 2 μg/kg, Group II with a mixture of 4% lignocaine 4 ml and dexmedetomidine 1 μg/kg, and Group III with 4% lignocaine 4 ml and saline. Results: Cough score was lower in Group II (1.6 ± 0.67) than Group I (2.5 ± 0.68) and Group III (2.7 ± 0.59). This difference between Group II and the rest of the group was highly significant (P < 0.001). Patients of Group II also had better satisfaction scores (1.40 ± 0.56) when compared to Group I (1.90 ± 0.71) and Group III (2.43 ± 0.57). Patients in Group II were more comfortable (1.23 ± 0.43) than Group I (1.63 ± 0.49) and Group III (1.87 ± 0.34) (P < 0.001). Conclusion: Dexmedetomidine as an adjuvant to lignocaine nebulization provides a better condition for bronchoscopy than fentanyl or lignocaine alone. Highlights: Flexible fiberoptic bronchoscopy (FFB) is used to diagnose diseases of the tracheobronchial tree, to obtain lung samples, to assist endotracheal tube/bronchial blockers/double lumen tube (DLT) etc. Methods used to anaesthetize the airway includes local anaesthetic nebulization, gargles, lozenges, sprays, and airway blocks during FFB. Common sedative agents used during awake FFB are benzodiazepines, opioids, and propofol. Dexmedetomidine as an adjuvant to lignocaine nebulization provides a better condition for bronchoscopy than fentanyl or lignocaine alone.